Hubungan Antara Profil Budaya Organisasi (Menggunakan Pendekatan Competing Values Framework) dengan Kinerja Organisasi Puskesmas di Kabupaten Jember Tahun 2012 (The Relationship between Organizational Culture Profile (using Competing Values Framework Appr - Tabita Rionica Ayu Wijayani; Sri Utami; Eri Witcahyo (Pustaka Kesehatan, 2014)
Community Health Center (CHC) is a technical execution unit of District Health Office which isvery important in society. Organizational performance of CHC in Jember Regency 2012 wasvery low. One of the factors that affects the organizational performance is organizationalculture. The study aims to analyze the relationship between organizational culture profile(using Competing Values Framework approach) with organizational performance of CHC inJember Regency 2012. The study is an analytical research with cross sectional approach.The determination of sample using proportionate stratified random sampling technique, withthe amount of sample is 33 CHC (723 respondents). Analysis of data in this study useLambda correlation statistic test (α=0,05). The result of the study showed that the dominantorganizational culture type of CHC located in hierarchy culture 78,79%, clan 12,12%, market9,09%, and adhocracy 0%. The result of Lambda correlation statistic test showed that thereis a relationship between organizational culture with organizational performance of CHC inJember regency (0,045 < α) and the rate of lowering error is 62,50%.Keywords: organizational culture, organizational performance, Community Health Center,Competing Values Framework.